Efficacy of fermented cereal flours and decomposed kitchen waste in - Kathar, Bablusing; Sharma, O P; Jain, H K (Indian Journal of Fisheries, 2011)
The present investigation was carried out for a period of 50 days in cement cisterns to evaluate the efficacies of fermentedrice (T1), maize (T2), wheat flour (T3) as well as decomposed kitchen waste (T4) in the production of microbial and zooplanktonpopulation. These were added @ 10 mg 1–1. The effect of different treatments on the bacterial and zooplankton populationwas quite significant. The average total bacterial population in 7 weeks duration was found to be highest (1817 No./ml) in T4,followed by T3 (1278 No./ml), T1 (1234 No./ml), and control (662 No./ml). Highest zooplankton population of 5553 No./1was obtained from T4 followed by T2 (4910 No./1), T3 (4357 No./1), T1 (3220 No./1) and control (2113 No./1). The resultsindicated highest efficacy of decomposed kitchen waste under the existing environmental conditions. The coefficient ofcorrelation between the average total bacterial population and average total zooplankton population was found significant.